Simulating the (99942) Apophis Earth Flyby Using a Contact Binary Model - Hai-Shuo Wang; Paul Sánchez; D.J. Scheeres (The Planetary Science Journal)
This paper investigates the mass shifts of asteroid (99942) Apophis during its 2029 close encounter with Earth, using the contact dynamics method, a type of discrete element method. Unlike previous analyses, we model the asteroid as a contact binary body with the addition of granules between the body’s components. To account for uncertainties in Apophis’ shape, we create eight multibody models, with a particular focus on a contact binary asteroid model featuring boulders concentrated in its neck region. Our simulations show that the inclusion of boulders, whether distributed across the surface or concentrated in the neck region, facilitates internal mass shifts, with minimal differences between models, indicating that boulder placement has little effect on the magnitude of the mass shifts. In polyhedral models, angularity dominates over friction and orientation. Spherical models are more sensitive to friction and orientation than shape. Both show minimal sensitivity to tensile strength. While we can find considerable shifts in the system for some parameter values, for values we consider more realistic, we find only modest deformation of the components and motion of surface material, on par with previous simulations. A critical stability threshold is identified at a neck size ratio of α  ≈ 0.4, below which contact binary asteroids become highly vulnerable to external perturbations and tend to reconfigure into more stable shapes.